Influences of Spillway Section Morphologies on Landslide Dam Breaching - Yang, Meng; Zhong, Qiming; Mei, Shengyao; Shan, Yibo (Frontiers in Earth Science, 2021)
Spillway excavation is often adopted as a precautionary engineering measure for disaster mitigation before landslide dam breaching. Based on the landslide dam breach mechanisms, this paper focuses on developing a numerical model to comprehensively discuss the issue based on three documented landslide dam failures, such as Tangjiashan, Xiaogangjian, and Baige landslide dams. The spillway cross section morphologies were modeled with different sizes under common shape (i.e., an inverted trapezoid) and slope conditions. The influence of cross section on dam breach processes was analyzed under conditions of different depth, bottom width, slope ratio in the cross and longitudinal sections, with/without spillway. The following conclusions can be drawn: 1) excavation of a spillway can effectively reduce the peak breach flow, therefore delay the time to peak; 2) the peak breach flow dramatically decreases and the time to peak delays as the spillway depth increases; 3) the peak breach flow changes little and the time to peak occurs earlier with the increment in spillway bottom width; 4) the peak breach flow decreases and the time to peak delays with the decrease of slope ratio in cross section in the spillway; 5) the slope ratio in the longitudinal section has little influence on the breach process. Hence, if conditions permit, the spillway with large spillway depth, small bottom width, and gentle slope ratio in the cross section is the preferable section morphology for the emergency disposal of the landslide dam.